PENENTUAN STRATEGI PENINGKATAN RETRIBUSI PELAYANAN PERSAMPAHAN/KEBERSIHAN PERMUKIMAN DI KABUPATEN SITUBONDO - Wulandari, Chusla Indah Ayu (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2017)
Abstract: The regional readiness to implement regional autonomy is measured from its financial capability that mainly sourced from the Regional Own-Source Revenue (PAD). The problem is that regional retributions as one of the PAD’s components have not been able to contribute significantly to the overall regional revenue. One of the causes is the lack of potential sources exploration. This also happened to the retribution of the waste management services of the settlement in Situbondo Regency. This study aims to identify opportunities, threats, strengths, weaknesses, and strategies that can be applied to increase the waste management services of the settlement in Situbondo Regency. The strategy is formulated by using Internal External (IE) and Strengths, Weaknesses,Opportunities, and Threats (SWOT) matrixes. Findings of the research show that opportunities and threats are consisted of the potential retributions payer, increasing numbers of housing, public awareness, parliament control, retribution rates, sanctions for the retribution payer, and competitors. The strengths and weaknesses are consisted of coordination between legislative party and relevant insitutions, the quantity and quality of the retribution collector, waste services, leakage control, quantity of the waste hauler, facilities and infrastructure, socialization, SOP, retribution tariff, and retribution contribution to the PAD. The main strategy to increase the revenue from the waste management service is the expansion strategy in the form of extensification by extending the coverage area of the retribution. Keywords: Strategy, Waste Services Retribution, Settlements.